ANALYSIS OF RISK FACTORS ECTOPIC PREGNANCY - Budi Santoso (Universitas Airlangga, 2017)
Introduction: Ectopic pregnancy is a pregnancy with extrauterine implantation. This situation is gynecologic emergency that contributes to maternal mortality. Therefore, early recognition, based on identification of the causes of ectopic pregnancy risk factors, is needed. Methods: The design descriptive observational. The samples were pregnant women who had ectopic pregnancy at Maternity Room, Emergency Unit, Dr. Soetomo Hospital, Surabaya, from 1 July 2008 to 1 July 2010. Sampling technique was total sampling using medical records. Result: Patients with ectopic pregnancy were 99 individuals out of 2090 pregnant women who searched for treatment in Dr. Soetomo Hospital. However, only 29 patients were accompanied with traceable risk factors. Discussion:. Most ectopic pregnancies were in the age group of 26-30 years, comprising 32 patients (32.32%), then in age groups of 31-35 years as many as 25 patients (25.25%), 18 patients in age group 21-25 years (18.18%), 17 patients in age group 36-40 years (17.17%), 4 patients in age group 41 years and more (4.04%), and the least was in age group of 16-20 years with 3 patients (3.03%). A total of 12 patients with ectopic pregnancy (41.38%) had experience of abortion and 6 patients (20.69%) each in groups of patients with ectopic pregnancy who used family planning, in those who used family planning as well as ectopic pregnancy patients with history of surgery. There were 2 patients (6.90%) of the group of patients ectopic pregnancy who had history of surgery and history of abortion. The incidence rate of ectopic pregnancy was 4.73%, mostly in the second gravidity (34.34%), whereas the nulliparous have the highest prevalence of 39.39%. Acquired risk factors, i.e. history of operations was 10.34%, patients with family planning 20.69%, patients with history of abortion 41.38%, patients with history of abortion and operation 6.90% patients with family and history of abortion was 20.69%.